(untitled) (Eurasian Journal of Research, Development and Innovation, 2024)
Analysis and comparison of some elements and standards for checks and water compared with standard specifications and our experience we took four samples of water in the residential neighborhood of Kirkuk Technical Institute And if you take 4 samples from the water of the residential neighborhood at the Kirkuk Technical Institute Show us that the Department of Metrology was within the boundaries of the world and some of them were not within the limits allowed for PH, TDS, BOD, Hardness, Flouride, Chlorine was within the limits of The EC, Turbidity were not within the limits .